Empowerment Strategy for School Dropouts Based on Entrepreneurship Education for Mocaf Flour Production at Pondok Roudlotuttholabah, Pemalang Regency - Jenifer Halim; Sungkowo Edy Mulyono (Jurnal Pemberdayaan Masyarakat, 2026)
Entrepreneurship education based on local potential, specifically mocaf flour production, at PKBM Pondok Roudlotuttholabah, Pemalang Regency. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, participant observation, and documentation involving program managers, tutors, learners, and business partners. The findings indicate that the empowerment strategy is implemented through four stages: planning, implementation, mentoring, and evaluation, which contribute to improving learners’ technical skills, entrepreneurial attitudes, and self-efficacy. The program also enhances learners’ readiness to establish small-scale businesses and strengthens social participation. The novelty of this study lies in the integration of local resource-based entrepreneurship education within non-formal education settings for school dropouts. This study contributes to the development of a contextual empowerment model that supports economic independence and strengthens the role of non-formal education in sustainable community development.